Integração econômico, crisa e emprego na Espanha. - Souza, Kayo Cicero Quirino de (2014)
This work is focused on the transformations undergone by the Spanish economy over the second half of the twentieth century and the first decade of this century, there included the 2008 crisis is analyzed as the process of economic integration of Spain, which had as dynamic pole of the real estate development impacted on the level of employment and income. Highlight the consequences that such a model resulted on the competitive dynamics of the country, causing greater vulnerability to economic crises. The paper points out that the construction industry spent over decades, as the sector that received government incentives since the period of Franco's dictatorship to the great crisis of 2008 In addition to these facts, it highlighted the importance of the financial sector served to deepen this model of development, to promote conditions conducive to the acquisition of homes by households, creating an innovative process that enabled converting the appreciation of property prices in liquidity for consumption. To enhance the level of employment was associated with the performance of the construction sector, an econometric estimation was carried out to verify this behavior for the period 1996 to 2012 The analysis is grounded in keynesian minskyana and theoretical approach.